Combination Therapy With Intensive Granulocyte and Monocyte Adsorptive Apheresis Plus Ustekinumab in Patients With Refractory Crohn's Disease. Issue 3 (23rd May 2018) - Tanida, Satoshi; Mizoshita, Tsutomu; Ozeki, Keiji; Katano, Takahito; Tanaka, Mamoru; Nishie, Hirotada; Shimura, Takaya; Okamoto, Yasuyuki; Kubota, Eiji; Kataoka, Hiromi; Joh, Takashi
Abstract: Ustekinumab is applied to induce clinical remission in patients with Crohn's disease. Granulocyte and monocyte absorptive apheresis depletes activated myeloid lineage leukocytes and has been applied for active Crohn's disease. This study retrospectively examined the efficacy and safety of combining intensive granulocyte and monocyte absorptive apheresis and ustekinumab for remission induction therapy in refractory Crohn's disease. Between June and September 2017, three consecutive cases (two females) with refractory Crohn's disease were treated with intensive granulocyte and monocyte absorptive apheresis plus ustekinumab. Crohn's disease activity index, and simple endoscopic score for Crohn's disease at baseline and 10 weeks were applied as treatment efficacy outcomes. In all three cases, at week 10, clinical remission was achieved, while simple endoscopic score for Crohn's disease reflected no improvement. Thus, combination therapy with intensive granulocyte and monocyte absorptive apheresis plus ustekinumab appeared to represent a safe and effective intervention for inducing clinical remission.